Public Service: Health Service Satisfaction at Dumai City Hospital - Hijeriah, E Maznah; Erlianti, Dila; Shaliza, Fara; Sofyan, Sofyan; Afrizal, Dedy (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
Dumai City Hospital activities center on community satisfaction. Improving the quality of health services is accomplished by enhancing the elements whose goal is to promote patient satisfaction. Several issues were discovered throughout its deployment, which became essential notes in carrying out its community activities. As a result, the purpose of this research is to examine service implementation, community satisfaction, and the effect of service on community satisfaction at the Dumai City Hospital. The study used a quantitative technique with 164 respondents and data analysis, especially descriptive statistics. The study's findings revealed that there was an impact of service on community satisfaction at the Dumai City Hospital. The advice given is to enhance the guaranteed waiting time for services that will be provided to patients, particularly in the acts of doctors at the Outpatient Polyclinic, in order to prevent complaints from the public due to the long wait to be serviced by a doctor. Furthermore, continue to enhance the skills of all staff so that they can better serve the community.